The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3329/ralf.v2i1.23034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indigenous medicinal plant Tulsi (Ocimum sanctum) leaves extract as a growth promoter in broiler

Abstract: The study was conducted to determine the efficacy of Tulsi (Ocimum sanctum ) leaves extract as a growth promoter in broiler. Thirty (30) day-old broiler chicks were purchased from Kazi hatchery and after seven days of acclimatization in the poultry shed of Pharmacology department randomly divided into two groups I0 and I1. No vaccination schedule was practiced and no antibiotics were added in rations. Group was supplemented with Tulsi (Ocimum sanctum) leaves extract @ 2ml/litre in drinking water. Weekly observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Similarly, statistical analysis of the data did not show any difference between the relative gizzard weights of the birds of respective groups but showed 1% level of significance of relative heart, liver, spleen and pancreas weight using drinking water with or without supplementation of tulsi leaves extract (Table 3). This results are also in accordance with the findings of Hernandez et al [19], Alom et al [20] who reported no differences in the mean weight of proventriculus, gizzard, intestine, liver and pancreas in broilers fed of two herbal plants extract. Relative weight (g) = Weight of organ / Live body weight of bird X 100…”
Section: Dressing Percentage and Weight Of Different Body Organssupporting
confidence: 93%
“…Similarly, statistical analysis of the data did not show any difference between the relative gizzard weights of the birds of respective groups but showed 1% level of significance of relative heart, liver, spleen and pancreas weight using drinking water with or without supplementation of tulsi leaves extract (Table 3). This results are also in accordance with the findings of Hernandez et al [19], Alom et al [20] who reported no differences in the mean weight of proventriculus, gizzard, intestine, liver and pancreas in broilers fed of two herbal plants extract. Relative weight (g) = Weight of organ / Live body weight of bird X 100…”
Section: Dressing Percentage and Weight Of Different Body Organssupporting
confidence: 93%
“…58±1.17, 34.72±0.54, 34.80±0.55, 37.86±1.42, 34.64±0.90, 38.32±2.39, 39.40±1.57, 34.70±2.46, 35.59±1.42 and 40.04±2.33, respectively in groups A, B, C, D, E, F, G, H, I and J. The results of the present study similar to the reports of Hasan et al (2016) and Alom et al (2015) for tulsi, Toghyani et al (2010) for peppermint, Khan et al (2012) and Toghyani et al (2010) for black cumin, Agboola et al (2018) for papaya.…”
Section: Packed Cell Volume (Pcv %)supporting
confidence: 91%
“…Then were chopped into small pieces by scissors and water was added at 1:10 ratio. The extract was prepared by mixing the leaves with pestle and motor and stored in a refrigerator at 4°C to maintain the active ingredients of the extract (Alom et al, 2015).…”
Section: Preparation Of Ocimum Sanctum Extractmentioning
confidence: 99%